Breastfeeding Patterns in Preterm Infants Born at 28-33 Gestational Weeks. (August 2015) - Oras, Paola; Blomqvist, Ylva Thernström; Nyqvist, Kerstin Hedberg; Gradin, Maria; Rubertsson, Christine; Hellström-Westas, Lena; Funkquist, Eva-Lotta
Background: Studies of breastfeeding patterns during preterm infants' first year of life are scarce but are important for providing breastfeeding mothers of preterm infants with optimal support. Objective: This study aimed to describe breastfeeding patterns in preterm infants up to 1 year of corrected age. Methods: As part of a larger study on kangaroo mother care in Sweden, a 24-hour breastfeeding diary was sent home after discharge from hospital, and at 2, 6, and 12 months of the infant's corrected age. Eighty-three mothers responded to the follow-up questionnaires, and the number of respondents to the breastfeeding diary was 48 at discharge, 43 at 2 months, 22 at 6 months, and 8 at 12 months. Infants were born at a median (range) gestational age of 32 (28-33) weeks. Breastfeeding patterns were analyzed according to durations, frequencies per 24 hours, and intervals between sessions. Results: In exclusively breastfed infants, the median (range) breastfeeding session frequency was 14 (8-26) times per 24 hours including 4 (1-9) times per night after discharge (n = 24) and 10 (6-25) times per 24 hours including 2 (0-5) times per night at 2 months (n = 23). In partially breastfed infants, the median (range) frequency was 5 (1-14) times per 24 hours including 2 (0-4) times per night at 6 months (n = 20) and 5.5 (1-12) times per 24 hours including 2 (0-3) times per night at 12 months (n = 8). Conclusion: Mothers reported large variations in breastfeeding patterns, with higher median breastfeeding session frequencies than previously described in term infants in affluent settings.